Severus of Antioch : his life and times - D'Alton, John (Priest) (Texts and Studies in Eastern Christianity, 2016)
Severus of Antioch: His Life and Times offers many fresh insights into the life, theology, reception history, exegetical approach, and asceticism of Severus, a key figure in the Oriental Orthodox Church, and central to the current discussions on Oriental Orthodox and Eastern Orthodox reunion. It includes articles from established Syriac scholars and theologians including well-known international authors Pauline Allen, Sebastian Brock, Rifaat Ebied and Ken Parry. The topics covered have immense theological and historical significance for the churches of the Middle East and the history of Late Antiquity, and explore new understandings of Severus' exegetical context, the theological and political impact of his sermons, and his relation to the many ideological currents of his time.